Juridical Analysis of Deeds of Peace Made in the Presence of a Notary in Resolving Civil Disputes Outside of Court - Zaenudin, Ahmad; Djunaedi, Djunaedi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
In resolving civil disputes, courts are often seen as the only way to achieve justice. However, in some cases, parties involved in a dispute can reach an amicable agreement outside of court through a mediation or negotiation process. One of the tools used to record this peace agreement is a peace deed made before a Notary. The reality that occurs in dispute resolution carried out by the courts is that it is considered slower and ineffective and is still felt to be detrimental by many parties. There are so many inherent weaknesses that it is considered necessary to have methods or institutions for resolving disputes outside of court even though the case has been tried in court. In this case the research focuses significantly and examines and discusses in order to be able to analyze so that one can find out about the Role and Responsibilities of Notaries in Settlement of Disputes Peacefully. In this case the responsibility of a Notary is not responsible for the contents of the deed made before him, but the Notary is only responsible for the formal form of an authentic deed as stipulated by law. This legal research also aims to determine the role of a notary in settlement with conciliation outside the court, the responsibility of a notary in resolving disputes against a deed of reconciliation made before a notary and to analyze research on the strength of law against a deed of reconciliation made before a notary. This type of research is sociological juridical research with an interview study approach, direct observation of several notaries who are experts in their field, as well as looking at the applicable laws and regulations (statute approach) which discuss the position of notary, and a case approach. The legal materials used in this legal research are primary legal materials with the data collection techniques used are interview studies and direct observation in the field.